1998
DOI: 10.1016/s0014-5793(97)01584-6
|View full text |Cite
|
Sign up to set email alerts
|

Specific effect of arachidonic acid on 17β‐hydroxysteroid dehydrogenase in rat Leydig cells

Abstract: It is well known that arachidonic acid (AA) acts as an intratesticular factor regulating luteinizing hormone-mediated testicular steroidogenesis. The present studies were conducted to determine the effect of AA on steroidogenic enzymes in rat Leydig cells. Exogenously added AA significantly inhibited 22(R)-hydroxy-cholesterol-stimulated testosterone production, which is a clear indication that AA is acting at some point after cholesterol transport to the inner mitochondrial membrane. AA failed to block the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…These cultured goat LCs possessed a typical spindle‐shaped morphology (Figure S3), and similar to the morphology of sheep LCs (Deng et al, 2018). In addition, we also showed that hCG or 22R‐OH‐cholesterol stimulated testosterone production in goat LCs in a dose‐dependent manner (Figure 2a,b), which is in line with observations from mouse LCs and rat LCs (Marinero et al, 1998; Wang et al, 2019). Moreover, hCG (5 IU/ml) stimulated intracellular cAMP production in goat LCs (Figure 2c).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These cultured goat LCs possessed a typical spindle‐shaped morphology (Figure S3), and similar to the morphology of sheep LCs (Deng et al, 2018). In addition, we also showed that hCG or 22R‐OH‐cholesterol stimulated testosterone production in goat LCs in a dose‐dependent manner (Figure 2a,b), which is in line with observations from mouse LCs and rat LCs (Marinero et al, 1998; Wang et al, 2019). Moreover, hCG (5 IU/ml) stimulated intracellular cAMP production in goat LCs (Figure 2c).…”
Section: Discussionsupporting
confidence: 91%
“…Twenty‐four hours later, the culture medium was removed and replaced with serum‐free M199 medium containing 0.1% BSA (Sigma‐Aldrich) and 1× AA. To measure the steroidogenic activity of LCs, we used 22R‐OH‐cholesterol (Sigma‐Aldrich) because it is more water‐soluble (Marinero et al, 1998). For the 22R‐OH‐cholesterol treatment experiment, goat LCs were incubated in the presence of different concentrations (0, 0.1, 0.5, 1, 3, 5, 10, 20, and 30 μM) of 22R‐OH‐cholesterol, and each concentration was used in triplicate (Marinero et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it has been reported that another cyclooxygenase inhibitor, indomethacin, is able to inhibit 3␤-hydroxysteroid dehydrogenase and 17␤-hydroxysteroid dehydrogenase activities in rat testis (22). On the other hand, more recently, it has been shown that AA by itself exerts a specific inhibitory effect on 17␤-hydroxysteroid dehydrogenase in rat Leydig cells (13). However, with regard to human testis, these possibilities seem to be unlikely because the present study indicates that aspirin treatment does not affect steroidogenesis in conditions of nonexposure to exogenous hCG.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that steroidogenesis is controlled by multiple signalling pathways. For example, cAMP/PKA pathways regulate steroid hormone biosynthesis by steady state levels of STAR protein (Manna & Stocco, ), and arachidonic acid (AA)‐mediated signal inhibits testosterone synthesis via blocking 17‐HSD protein activity (Marinero et al, ), whereas for females, the levels of P4, E2 and T are changed along with oestrus and gestation. Thus, the mechanisms of steroidogenesis are more complicated than previously thought in ovary.…”
Section: Introductionmentioning
confidence: 99%